Do submerged macrophyte species influence crustacean zooplankton functional group richness and their resource use efficiency in the low-light environment? - Wang, Li; Ma, Xufa; Chen, Jun (Frontiers in Plant Science, 2023)
During the high grazing of epiphytic zooplankton in submerged macrophyte beds, the changes in crustacean zooplankton functional groups are crucial for stabilizing a clear water state in shallow lakes. However, submerged macrophytes often experience low-light stress due to many ecological processes. It is unclear whether submerged macrophytes alter the zooplankton functional group and their resource use efficiency in the low-light environment. We conducted two mesocosm experiments involving the treatments of low-light and submerged macrophyte species (Vallisneria natans and Potamogeton maackianus). The results show that abiotic factors (e.g., light) were the most important variables in explaining the change in the zooplankton community. Specifically, zooplankton functional group (i.e., pelagic species, plant-associated species, and substrate scrapers) richness and zooplankton species diversity decreased with the decreasing light intensity, especially for low substrate scraper abundance. In addition, structural equation models showed that low-light stress reduced zooplankton resource use efficiency by reducing zooplankton functional group richness and species diversity. Compared to species diversity, zooplankton functional group richness had a greater influence on their resource use efficiency (Zp/Chl-a) in the low-light environment. Our results suggest that the low-light stress reduced zooplankton resource use efficiency by changing their functional group richness. Moreover, the abundance of substrate scrapers shaken from V. natans was higher than that from P. maackianus. Therefore, submerged macrophyte species influence crustacean zooplankton functional group richness and their resource use efficiency in the low-light environment. Selecting appropriate aquatic plant species to assure the high diversity of zooplankton should be considered when conducting lake restoration using submerged macrophytes.